6(3.14)=w-6(3.14)

Simple and best practice solution for 6(3.14)=w-6(3.14) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(3.14)=w-6(3.14) equation:


Simplifying
6(3.14) = w + -6(3.14)

Multiply 6 * 3.14
18.84 = w + -6(3.14)

Multiply -6 * 3.14
18.84 = w + -18.84

Reorder the terms:
18.84 = -18.84 + w

Solving
18.84 = -18.84 + w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-1w' to each side of the equation.
18.84 + -1w = -18.84 + w + -1w

Combine like terms: w + -1w = 0
18.84 + -1w = -18.84 + 0
18.84 + -1w = -18.84

Add '-18.84' to each side of the equation.
18.84 + -18.84 + -1w = -18.84 + -18.84

Combine like terms: 18.84 + -18.84 = 0.00
0.00 + -1w = -18.84 + -18.84
-1w = -18.84 + -18.84

Combine like terms: -18.84 + -18.84 = -37.68
-1w = -37.68

Divide each side by '-1'.
w = 37.68

Simplifying
w = 37.68

See similar equations:

| ((x-1)/3)-2=((x-5)/4) | | 2x+18y=18 | | 3x-11=2x+33 | | 14-b=8 | | -4+3x=7x+x+14x-8x | | 65=-6-x | | 81=x+181 | | 6/10-2/100 | | V-10=-19 | | -4+3x=7x+x+14-8x | | 9a-6=8a+1 | | 2x+2x+x+3x+3=24 | | 2x+0=5y-0 | | 5x+6=9x+3+8x | | 7bf^4-7bk^4= | | 6u(-5u^4)=0 | | 2a-1=3(a+1)+7a+5 | | X+4+5x+3+4x=21 | | (y^-1/4)^1/6 | | 9-3v=0 | | 17x-36=12x+7 | | x+8=-72 | | 2(x-6)=3(x-4) | | y^(3/2)-10y | | 18=x/7 | | 66=1.5x | | -5(6y-6)-y=-3y(y-5) | | 16a^4+36a^3b-10a^2b^2= | | 5(7n-4)-3= | | -0.666+4w=-0.111 | | -7+4(1+5a)= | | 9xa+1=8a |

Equations solver categories